Socio-cultural Sustainability for Resilience in Public Services: Strategies for Achieving Inclusive and Equitable Service Delivery - BURLACU, Sorin; RĂDULESCU, Carmen-Valentina; BĂLU, Evelina Petronela; DOBRE, Florin (European Journal of Sustainable Development, 2023)
Socio-cultural sustainability has become an increasingly important aspect of resilience in public services, particularly in meeting the needs of diverse populations. This article reviews the concept of socio-cultural sustainability and its relevance to public services and provides a comprehensive framework for achieving socio-cultural sustainability in service delivery. The framework includes five key strategies: (1) engaging with diverse communities, (2) promoting cultural competency, (3) fostering inclusion and equity, (4) building partnerships, and (5) continuous evaluation and improvement. The article discusses the importance of each strategy and provides practical examples and case studies to illustrate how they can be implemented in practice. The research explores the benefits of achieving socio-cultural sustainability, including increased community engagement, improved service delivery, and enhanced organizational performance. Finally, the article discusses the challenges of achieving socio-cultural sustainability in public services and provides recommendations for overcoming these challenges. Keywords: socio-cultural sustainability, resilience, public services, strategies